COSTUMER PROTECTION AGAINST CIRCULATING OF PRODUCT WITHOUT INFROMATION ATTECMENT IN BAHASA INDONESIA - Tomy Yoanes; Iriansyah Iriansyah; M. Yusuf Daeng (STIH Putri Maharaja, 2021)
Based on Article 8 Paragraph (1) Letter j Law Number 8 of 1999 concerning on Consumer Protection, it states that business agents are prohibited to produce and / or trading goods and / or services for do not provide the information and / or instructions for using the goods in Indonesian. This research aims to explain of the legal protection of consumers for the distribution of food and beverage products that do not include the information of the product in Bahasa in Bengkalis Regency based on the legislation of Indonesia Number 8 of 1999 about the regulation of Consumer Protection. The method used in this research is socio-legal research. The results of the research explains that the legal protection of consumers for the distribution of food and beverage products for do not include information in Bahasa in Bengkalis Regency has not been implemented verywell; because circulating of food and beverage products in Bengkalis Regency have distributed to local market places without providing product’s information in Bahasa. The legal consequences for consumers for the circulation of food and beverage products without providing product’s information in Bahasa can be detrimental for consumers because consumers can not find information about these food and beverage products as well as the contents and the ingridiances of the product , including whether or not such food and beverages are dangerous.